"Social", "Open" and "Participative"? Exploring Personal Experiences and Organisational Effects of Enterprise2.0 Use - Denyer, David; Parry, Emma; Flowers, Paul (Elsevier Science B.V., Amsterdam., 2011)
Organisations are increasingly adopting Web2.0 technologies such as web-based communities, social networking sites, wikis and blogs to enable users to interact, share information and alter web-based content. In a business/ commercial context, the use of such technologies has been termed Enterprise2.0. This paper explores organisational actors’ experiences of this new technology and how the shift to Enterprise2.0 is shaping how people work and organise. We present an in-depth case study of a large multinational telecommunications company that is commonly regarded as one of the leading proponents of Enterprise2.0. Data were collected from three business units each exhibiting different characteristics in terms of the level of Enterprise2.0 experience and employee participation in decision-making. Our findings show that while Enterprise2.0 is claimed to be “social”, “open” and “participative” and has the potential to deliver significant business benefits, the experiences of organisational actors suggest that their expectations regarding Enterprise2.0 use were not met. Paradoxically, employee participation was limited and the monitoring and moderation of certain discussions, together with political use of the technology by leaders, meant that the use of Enterprise2.0 was often thought of as no more “social”, “open” or “participative” than more traditional methods of communication. These results are discussed within the framework of previous research on the management of the introduction of new technology and its use and exploitation within organisations.